2019
DOI: 10.1002/ijc.32718
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory serum markers and risk and severity of prostate cancer: The PROCA‐life study

Abstract: Whether chronic inflammation mirrored by high levels of systemic inflammatory markers such as high sensitive-CRP (hs-CRP) and white blood cell count (WBC) are associated with prostate cancer development remains unclear. In the Prostate Cancer Study throughout Life (PROCA-life), a prospective population-based cohort study, 7,356 men were included. Prediagnostic WBC and hs-CRP were assessed from blood collected at study entry; 2,210 participants also had a second CRP measure during follow-up. During a mean 11.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…They found that inflammatory biomarkers were associated with cancer risk and mortality [18]. Another study showed that in addition to high-sensitivity C-reactive protein (hs-CRP) being able to evaluate the risk of cardiovascular diseases, increasing concentrations of hs-CRP in serum also correlated with prostate cancer risk and prognosis [19]. Abnormal levels of inflammation-related serum proteins, such as C-X3-C motif chemokine ligand 1, platelet-derived growth factor subunit B homodimer, interleukin 10, C-C motif chemokine ligand (CCL) 21, and CCL 11, were also found to be related to the risk of prostate cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…They found that inflammatory biomarkers were associated with cancer risk and mortality [18]. Another study showed that in addition to high-sensitivity C-reactive protein (hs-CRP) being able to evaluate the risk of cardiovascular diseases, increasing concentrations of hs-CRP in serum also correlated with prostate cancer risk and prognosis [19]. Abnormal levels of inflammation-related serum proteins, such as C-X3-C motif chemokine ligand 1, platelet-derived growth factor subunit B homodimer, interleukin 10, C-C motif chemokine ligand (CCL) 21, and CCL 11, were also found to be related to the risk of prostate cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…Because circulating C-reactive protein (CRP) is an important biomarker for low-grade chronic inflammation, the association of this biomarker with the incidence of prostate cancer has been investigated in several observational epidemiological studies. Some prospective studies found a positive association of CRP with risk of prostate cancer ( 4 6 ), but others did not provide evidence to support this relationship ( 7 11 ). Moreover, because conventional observational studies are susceptible to potential bias such as unmeasured confounders and reverse causality, it remains unclear whether the association of CRP with prostate cancer risk is causal or not.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation is thought to promote carcinogenesis and markers of systemic inflammation may be indicative of increased prostate cancer risk [41,42]. However, in our study,…”
Section: Discussionmentioning
confidence: 54%